Visual Aesthetics Understanding of Elementary Students in Creating the Artworks - Probosiwi Probosiwi; Yuni Hastuti (International Journal of Visual and Performing Arts, 2019)
This research has motivated by the author's desire to know deeply about elementary students' understanding of visual aesthetics through the objectification process. The purpose of this research is to explore the ability of elementary school students to interpret the beauty and visual arts through practical activities in making three-dimensional artworks. The author using qualitative research methods with data collection techniques are observation, interviews, and document reviews. The subjects are students in Grade 6 at SD Negeri Bhayangkara Yogyakarta. The data analysis technique used is narration. The results are obtaining students taking the stages in making artworks with a visual aesthetic approach and the objectification process towards natural objects. Visual aesthetic understanding for elementary students comes from how we can invite them doing practicing at outclass and let them look for reference from many sources. Creativity reveals from combining person, product, process, and environment. The involvement of the lecturer and tutor teacher in the learning process is beneficial for students in representing ideas and ideas. Besides, the process of mentoring during practice can control the attitudes of those who tend to play around still.